Fair value disclosure, liquidity risk and stock returns - Roggi, Oliviero; Giannozzi, Alessandro (Journal of Banking & Finance, 2015)
This paper aims to investigate the impact of company liquidity risk on the stock prices of financial and non-financial companies by analyzing investors’ reactions to 106 crisis events over the period from 2008 to 2010. Companies’ liquidity risk shows up in the three levels of fair value information (level 1-mark to market, level 2-market observable input and level 3-mark to model) disclosed in their balance sheets, with level 3 illiquid assets representing a greater liquidity risk and resulting in a greater company liquidity risk. The role played by liquidity risk information in investors’ decision-making is explored by analyzing their reactions to liquidity-constraining events, capital injections and bank bailouts for 313 European companies. The empirical evidence is based on the fixed effects model and Partial Least Squares regressions. These findings demonstrate that investors’ reactions to the crisis events are affected by the liquidity risk conveyed by the levels of fair value hierarchy in both financial and non-financial firms. During liquidity-constraining events, investors have stronger negative reactions to companies with more level 3 illiquid assets and liabilities on their balance sheets. During liquidity-expanding events, investors react more positively to companies with more illiquid assets.